Implementasi Kebijakan Tentang Penciptaan Budaya dan Iklim yang Kondusif di Sekolah - Sarah Dalila Fitri; Fitriana Yasintha; Revi Yulianti (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
This article discusses the implementation of policies to create a conducive school culture and climate as an important part of efforts to improve the quality of learning. A safe, comfortable, and orderly learning environment is essential for effective and enjoyable learning. This study aims to analyze the strategies and roles of the principal and all school members in shaping a positive school culture and climate. The main focus lies on four managerial aspects: program planning, organization, leadership implementation, and structured control. This study uses a qualitative method with a case study approach, applied in several elementary schools. Data were collected through field observation techniques, in-depth interviews with related parties (such as the principal, teachers, and students), and documentation studies of school policies and programs. The main findings indicate that a conducive school culture and climate are formed through a series of consistently implemented positive habits, strong collaboration among school members, and the visionary and communicative leadership of the principal. In addition, the active involvement of all school elements in creating an atmosphere of mutual respect and support is very influential in building a positive learning environment. Policy implementation is not merely administrative, but also emphasizes the development of character values, discipline, and a sense of shared responsibility. The end result is improved learning quality and improved student character, demonstrating that school climate and culture play a crucial role in the overall educational process.